Development of Scientific-Based Thematic Worksheets to Improve Cognitive and Language Abilities of Children Aged 5-6 Years - Mawarti Nyoto Prawiro; Hendratno; Budi Purwoko (Studies in Philosophy of Science and Education, 2023)
This study introduces a novel approach by utilizing distinct thematic worksheets with a scientific framework to actively engage 5-6-year-old children in critical thinking through the scientific process. The worksheets appreciate cognitive development, analytical skills, and higher-order thinking. This innovative method encourages active participation and the development of cognitive and analytical abilities in children. The research focuses on the development of scientific-based thematic worksheets to enhance the cognitive and language abilities of 5-6-year-old children in PAUD, specifically at the Soleh Children Education Park (TAPAS) in Taman District, Sidoarjo Regency. The study employed a quantitative approach with a one-group pretest-posttest design, involving 21 children as research participants. The development process followed the Research and Development (R&D) framework, comprising 10 stages. Data collection included the validation of the worksheets by subject matter and media experts to assess their feasibility. The findings highlight the effectiveness of the scientific-based thematic worksheets, as demonstrated by significant improvements in the cognitive and language abilities of the 5-6-year-old students at TAPAS. Overall, this study contributes to early childhood education by introducing an innovative educational resource that enhances critical thinking skills and promotes deeper understanding among young learners.